Pengaruh Ikonik dan Aksesibilitas Terhadap Minat Kunjungan Wisatawan di Desa Wisata Loha - Kapra Ade Hedri Yusta; Septy Indrianty; Lia Afriza (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2026)
The growth of the tourism sector in Indonesia has shown rapid development along with the increasing number of tourist visits. On the other hand, public interest in the concept of tourism villages is also relatively significant, as reflected in Google Trends data in 2025. This study aims to analyze the effect of Iconicity and Accessibility on Tourist Visit Intention in Loha Tourism Village. The method used is a quantitative approach. The population in this study consists of all tourists visiting Loha Tourism Village, with a sample of 100 respondents. Data collection was carried out through questionnaires, and then analyzed using descriptive and verification approaches with the assistance of SPSS version 25. The independent variables in this study are Iconicity (X1) and Accessibility (X2), while the dependent variable is Tourist Visit Intention (Y). The results of the descriptive analysis show that the average value of the iconic variable is 3.90, accessibility is 3.53, and visit intention is 3.89, all of which are in the good category. Meanwhile, the verification analysis results indicate that partially, iconicity has a positive and significant effect on visit intention, while accessibility has a negative and insignificant effect. However, simultaneously, both variables have a significant effect with a contribution of 61.60% to tourists’ visit intention in Loha Tourism Village, while the remaining 38.40% is influenced by other factors beyond the scope of this study.